2013
DOI: 10.1371/journal.pone.0076557
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Novel Anti-Nicotine Vaccine: Influence of Antigen Design on Antibody Function in Mice

Abstract: Anti-nicotine vaccines may aid smoking cessation via the induction of anti-nicotine antibodies (Ab) which reduce nicotine entering the brain, and hence the associated reward. Ab function depends on both the quantity (titer) and the quality (affinity) of the Ab. Anti-nicotine vaccines tested previously in clinical studies had poor efficacy despite high Ab titer, and this may be due to inadequate function if Ab of low affinity were induced. In this study, we designed and synthesized a series of novel nicotine-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 35 publications
(48 reference statements)
0
92
0
Order By: Relevance
“…Such conjugation requires attachment of the hapten to the carrier protein, usually via a linker, which can vary in length, rigidity and hydrophilicity. The nicotine hapten, carrier protein, linker and handle to attach the hapten to carrier can all contribute to the immunogenicity of the nicotine conjugate antigens [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Such conjugation requires attachment of the hapten to the carrier protein, usually via a linker, which can vary in length, rigidity and hydrophilicity. The nicotine hapten, carrier protein, linker and handle to attach the hapten to carrier can all contribute to the immunogenicity of the nicotine conjugate antigens [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These masked compounds in the squaryl entity would benefit further chemical transformations especially allowing for conjugation of biomolecules. These may include Kitson monoclonal antibodies, proteins and novel anti-nicotine vaccines [111]. Table 2 demonstrates the potential usage of squaryl molecular metaphors showing a variety of transformations to give carbonyl functionality.…”
Section: Figure 22 Tetrazole -Semisquarate Interchangementioning
confidence: 99%
“…75,[85][86][87] Increased efficacy of a heroin vaccine correlated with higher haptenization ratios in conjugates containing a tetanus toxoid (TT) carrier but not the diphtheria toxin crossreactive material (CRM 197 ) carrier. 88 Yet, haptenization ratio did not correlate with anti-heroin Ab titer nor affinity.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
“…87 This impressive effort yielded a lead immunogen consisting of the 5-aminoethoxy-nicotine (Hapten 7) conjugated to CRM 197 . 87 The optimized NIC7-CRM 197 adsorbed on alum plus the toll-like receptor (TLR) 9 agonist CpG adjuvant showed promising pre-clinical efficacy in both mice and NHP, 46,87,89 and these candidates were recently evaluated in a clinical trial ( Table 1). Analysis of several lots of NIC7-CRM 197 showed that higher vaccine immunogenicity and efficacy correlated to lower degree of conjugate aggregation, and minimal presence of adducts.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%